Answers

2016-03-27T23:24:35+05:30
Let us consider smaller part as X, then larger part is 23-X.
According to problem,
3X=2(23-X)+9
3X=46-2X+9
3X+2X=46+9
5X=55
X=11

So,Smaller part is 11.
Larger part is 23-11=12.
0
2016-03-28T12:51:32+05:30
Let the smaller no= x
let the larger no= y

x + y = 23...
it means that
y = 23 - x.........(i)
Acco to question...
3x = 2y + 9.....(ii)
now put value of y in (ii)
by putting y we get..
3x =2(23-x)+9
3x= 46- 2x + 9
3x+2x = 46+9
5x = 55
x = 55/5
x = 11........
now put value of x into (i)
y = 23 - x
y = 23 - 11
y = 12...
hence value of x = 11...
and value of y = 12
hope it helped...
please mark it as brainliest
0